Association of Perioperative Complications with Vitamin D Levels in Major Head and Neck Surgery. (13th August 2021) - Groysman, Matthew; Bearelly, Shethal; Baker, Audrey; Wang, Steven J.; Symms, John
Abstract : Objectives/Hypothesis: To investigate the association of vitamin D level and perioperative complications in patients undergoing major head and neck surgery. Study Design: Retrospective Cohort Study. Methods: A retrospective chart review was performed for all patients undergoing reconstructive head and neck surgery between December 2017 and December 2019. Data regarding patient demographics, serum 25‐hydroxyvitamin D (calcidiol) level, hospital course, prior radiation, and fistula formation were collected. Patients were categorized by serum calcidiol level as deficient (<20 ng/mL) or sufficient (≧20 ng/mL) and outcomes were compared between groups. Results: Fifty‐seven patients were included in the analysis. Average age at time of surgery was 62.6 ± 10.6 years. Patients with vitamin D levels <20 ng/mL were considered deficient and ≧20 ng/mL were considered sufficient. Individuals in the deficient group (n = 29) had a mean serum calcidiol level of 13.95 ± 3.95 ng/mL, whereas those in the sufficient group (n = 28) had a mean calcidiol level of 28.53 ± 5.73 ng/mL. The rate of fistula was 41.4% in the deficient group, whereas patients in the sufficient group had a rate of fistula of 14.3% ( P  = .038). On multivariate analysis, higher serum calcidiol level above 20 ng/mL was associated with a lower likelihood of developing fistulae with an odds ratio 0.830 (95% confidence interval: 0.718–0.960, P  = .012). Conclusion: Vitamin D deficiency may play a role in development of fistula after major head and neck surgery. Level of Evidence: 4 Laryngoscope, 132:578–583, 2022